High expression of nucleobindin 2 is associated with poor prognosis in gastric cancer - Bolag Altan; Kyoichi Kaira; Shuichi Okada; Tsugumichi Saito; Eijiro Yamada; Halin Bao; Pinjie Bao; Kengo Takahashi; Takehiko Yokobori; Oyama Tetsunari; Masahiko Nishiyama; Masanobu Yamada (Tumor Biology)
Nucleobindin 2 has been reported that its high expression is associated with poor outcome and promotes cell migration and lymph node metastasis in breast cancer, colon cancer, and prostate cancer. However, we aimed to investigate the nucleobindin 2 expression in gastric cancer tissues and adjacent non-tumor tissues and its potential relevance to clinicopathological factors and prognosis using immunohistochemical analysis. In our study, nucleobindin 2 level in gastric cancer tissues was higher than in non-tumor tissues. A high expression of nucleobindin 2 is significantly associated with tumor depth, lymph node metastasis, lymphatic invasion, venous invasion, and clinical stage. Furthermore, the expression level of nucleobindin 2 protein was independent predictor of progression-free survival. In summary, nucleobindin 2 might play a crucial role in gastric cancer development and could serve as an independent predictor of prognosis of gastric cancer patients.